A cachaça nos dois lados do Atlântico: produção comércio e proibição - Ricardo, Raphael Martins [UNESP] (2014)
In the brazilian colonial period, mainly between the years of 1640 and 1695, the cahaca's production and commercialization had suffered innumerable legislative measures by the Portuguese Crown in order to regulating these activities, to the point of being forbidden. This attitude was motivated by the constant claims of the portuguese producers of wine who pointed the drink as they direct competitor and responsible for the fall of the sales of their product. Moreover, it had masters of sugar mill's claims, which passed for difficulties generated by the competition of the sugar produced in the Antilles, that the Crown to take some measure against the manufacture of the drink, therefore was they direct competition in the commerce of the sugar cane and firewood (used in the stills/alambique). Amid these commercial and economic order conflicts, the Jesuit priests also were hostile to the cachaça's consumption, since they blamed it for the degeneration of the indians and slaves bodies and souls. All these tensions left the Crown in a delicate position, therefore cachaça was the main product in the African commerce of slaves and responsible for the reorganization of a regular commerce between Brazil and the African trade. In this sense, this project has as main objective to analyze the economics and politics impediments for which cachaça´s production passed during this period, trying to understand the complicated situation of the Crown, that depended of incomes proceeding from distinct sources, not being able, therefore, unconditionally ally itself to one of the sides. Reason of their vacillating attitude, sometimes forbidding the cachaca's production, sometimes authorizing and being rigid